African laicities as seen from Bamako: a symposium taken by its context - (:unkn) unknown (My University, 2013)
Laicity is a buzzword in France, but it's also a buzzword in French-speaking countries, from Canada to Mali, via Belgium, the Comoros and Senegal. Yet laicity is no less difficult to define, especially when it is perceived and used - as is often the case - in its singular, tautological form. In West Africa, where the democratization of the 1990s brought about profound changes in political regimes, laicity appears to be a symbolic and political word that mainly drives social debate (power relations) and societal debate (value relations), rather than a real legal concept for describing relations between politics, religion and society.
Keywords: African Research